Kajian Paham Utilitas dan Manfaat Pendidikan Seni Bagi Anak Usia Dini - Grandena, Egi Putri (TACET Jurnal Pendidikan dan Kajian Seni, 2022)
To appreciate art and education as a whole requires access to discussions from various dissections of study with certain theories. In this paper, the author examines utility theory in relation to the benefits of arts education as a whole. As utility is an understanding with the principle of priority, namely efforts to fully maximize welfare or principles that prioritize the achievement of a sense of human happiness. In this paper, the author examines the principle of utility and the benefits of art education for early childhood so that they can explore the importance of art education as a whole for growth and development in early childhood. Children at an early age range between the ages of 0-6 years and this is the golden age. During the golden age, all child development can jump very drastically. At this age stage it is important to instill basic education which will become the basic foundations that are important for the growth and development of children. Thus, early childhood get provision of basic values that are instilled from an early age, as a preparation to go to the next level of education, namely the elementary school level.